Benchmarking the natSi(p,p0) and natO(d,d0) elastic scattering and the 16O(d,p0,1,α0) reactions for IBA purposes - Dede, S.; Kokkoris, M.; Lagoyannis, A.; Paneta, V.; Preketes-Sigalas, K.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
The benchmarking experimental procedure in IBA (Ion Beam Analysis) is carefully designed in order to validate evaluated and experimental differential cross–section datasets of charged particles via the acquisition of EBS and NRA spectra from thick targets of known composition, followed by their simulations. In the present work, such benchmarking measurements have been performed at the laboratory of the Institute for Nuclear and Particle Physics “Demokritos”, for the elastic scattering of protons on natSi in the energy range of 1.1 – 3.5 MeV at four backward angles, at 140o, 150o, 160o and 170o. In addition, measurements were performed for the elastic scattering of deuterons on 16O in the energy range of 1.1 – 1.7 MeV at four backward angles, at 140o, 150o, 165o and 170o. More specifically, a thick non–polished Si target with Au evaporated on top and a Nb2O5 tablet were used. The spectra acquired were compared with simulated ones using the SIMNRA program along with the evaluated differential cross-section datasets from IBANDL. All the experimental parameters were thoroughly investigated. The obtained results, the observed discrepancies and the encountered problems during the benchmarking process are discussed and analyzed.